Electrocatalytic hydrogen redox chemistry on gold nanoparticles - Brust, Mathias (2012)
Electrocatalytic proton reduction leading to the formation of adsorbed molecular hydrogen on gold nanoparticles of 1-3 and 14-16 nm diameter stabilized by 1-mercapto-undecane-11-tetra(ethyleneglycol) has been demonstrated by cyclic voltammetry using a hanging mercury drop electrode. The nanoparticles were adsorbed to the electrode from aqueous dispersion and formed robust surface layers transferrable to fresh base electrolyte solutions. Unique electrocatalytic proton redox chemistry was observed that has no comparable counterpart in the electrochemistry of bulk gold electrodes. Depending on size, the nanoparticles have a discrete number of electrocatalytically active sites for the two-electron/two-proton reduction process. The adsorbed hydrogen formed is oxidized with the reverse potential sweep. These findings represent a new example of qualitative different behavior of nanoparticles in comparison with the corresponding bulk material.